EXPLORATION OF THE ONTOLOGY OF THE GUIDANCE AND COUNSELING PROFESSION: A SYSTEMATIC REVIEW OF THE CONCEPT, ROLE AND IDENTITY OF COUNSELORS - Nuraini Nuraini; Edi Purwanta; Diana Septi Purnama (LP2M IAI Al-Khairat Pamekasan, 2026)
The Guidance and Counseling (BK) profession is developing in line with the complexity of the needs of students and the demands of the professionalism of counselors. This study explores the ontology of the BK profession systematically, focusing on the concept, role, and professional identity of counselors. The method used is a Systematic Literature Review (SLR) based on PRISMA, with an analysis of 7 selected scientific articles. The results show that counselors' professional identities are a dynamic construct formed through accredited education, practical experience, regulation, collective advocacy, cultural context, spiritual values, and social orientation. The role of a counselor is multidimensional, encompassing individual practice, leadership, advocacy, and social engagement, while the concept of a counselor encompasses professional knowledge, skills, and values. The ontology of the BK profession emphasizes that the reality of counselors is progressive, subjective, and contextual. Strengthening professional identity is the foundation of competence, ethics, and sustainability of BK services.